2010
DOI: 10.1097/01.asw.0000383752.39220.fb
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Therapy Accelerates Healing of Stage I Pressure Ulcers in Older Adult Patients

Abstract: Based on these results, the use of the vibrator may facilitate the healing of Stage I PrUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 16 publications
(13 reference statements)
1
47
0
Order By: Relevance
“…Furthermore, such interventions may help in accelerated healing of chronic wounds like pressure injuries or diabetic ulcers, etc (Arashi et al. ; Weinheimer‐Haus et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, such interventions may help in accelerated healing of chronic wounds like pressure injuries or diabetic ulcers, etc (Arashi et al. ; Weinheimer‐Haus et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as a noninvasive therapeutic modality with the potential to improve or restore blood flow, intervention with WBV would be of utmost importance for the subjects with impaired peripheral circulation. Furthermore, such interventions may help in accelerated healing of chronic wounds like pressure injuries or diabetic ulcers, etc (Arashi et al 2010;Weinheimer-Haus et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbaric oxygen therapy and vibration therapy have been found to promote PU healing. [30][31][32] These methods, which are contactless and comfortable for patients, may also help prevent PU by improving tissue hypoxia and HIF-1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous studies reported that this device can be safely used for elderly individuals. 22 The vibrator was placed under the legs with cushions between them ( Figure 1). Vibrations were performed three times: morning (06:00-09:30), day (12:30-14:30), night (18:00-21:00), and each vibration was performed for 15 min.…”
Section: Interventionmentioning
confidence: 99%